Caracterização anatômica da madeira de três espécies do Semiárido - Paula, Yara Lemos de (Universidade Federal Rural do Semi-Árido, 2018)
While of intense use of native species of Caatinga for energy purposes, their characteristics and properties are poorly known. The completion of knowledge of these attributes could help in the efficient and appropriate use of this material, guide in the search of new uses, and develop a tool for the identification and supervising these species in native wood trade in Northeastern of Brazil. Parameters such as the basic specific gravity and the anatomy are regularly used in studies on the wood characterization. The aim of this study was to obtain the basic specific gravity and to realize a macroscopic and microscopic wood anatomic characterization of three native species of Caatinga: Catingueira (Poincianella pyramidalis (Tul.) L.P. Queiroz - Fabaceae), Jurema-preta (Mimosa tenuiflora (Willd.) Poir.- Fabaceae) e Pau-branco (Cordia oncocalyx Allemão – Boraginaceae). Sample analysis followed the usual methods of wood anatomy studies: NBR 11941 to define the basic specific gravity of woods, COPANT, IPT workbook and IAWA to define the macroscopic and microscopic wood anatomic characterization. The woods have medium to high basic specific gravity, heartwood and sapwood are distincts, straight grain, medium- to coarse-grained texture, smell/taste and exudation absents,it may be natural durability, color and striking figure; axial parenchyma is paratracheal and it may be aliform with confluence porous visible to naked eye, small to medium, solitaries and multiples, very rarely to rarely frequents, diffuse-porous, scalariform and foraminate perforation plates, rays visible to naked eye, biseriates to multisseriates, non- and storied, homogeneous and heterogeneous, shorts, thins and very low frequents, shorts fibres with thin- to thick-walled. From some characteristics analyzed, it was observed that the three woods have others potential uses apart from power generation. This information is also important to encourage for the new research, to guide decision-making on the use in the most efficient and appropriate for these woods and to strengthen the enhancement and sustainable use of species of Caatinga.
Monografia
Keywords: Desenvolvimento Rural; Engenharia florestal; Microscopia; Sustentabilidade; Usos Múltiplos; Forest Engineering; Microscopy; Multiple Uses; Rural Developm; Sustentability; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL